Pengembangan Kristo Rai sebagai Wisata Alternatif di Area Branca Timor Leste - I Made Mardika; Ni Luh Made Mahendrawati; Anak Agung Ayu Dewi Larantika; Ni Made Jaya Senastri; I Ketut Kasta Arya Wijaya; Leonito Reiro; Mateus Ximenes (Universitas Warmadewa, 2025)
Timor Leste is currently developing the tourism sector to support the national economy. One of the tourism potentials being developed is the Branca Area, particularly the Kristo Rei statue, which has not developed as expected since its construction in 2000. In this regard, the Warmadewa University Team, in collaboration with DAPAZ University and the Timor Leste Institute of Business (IOB), implemented a Community Service (PKM) program with the topic